From Inert Carbon Dioxide to Fuel Methanol by Activation in Plasma Atmosphere. (March 2015) - Suarez, Alejandro; Leal-Quiros, Edbertho; Gonzalez, Jorge
Abstract: The electron-molecules collisions in plasmas are fructiferous field of study, particularly in activation of inert species into extremely active chemical reactants. Several gases such as carbon dioxide, methane, nitrogen, argon, water among others are ionized or simply activated under collisions with electrons creating the complex atmosphere plasmas. Based upon the energy distribution of electrons and the cross section of molecules it is possible to stimulate molecules becoming highly active species. This research explores the assembly of methanol over a surface of Cu-O-Zr catalyst when carbon dioxide reacts with water under the plasma developed into the Electron Cyclotron Resonance device (ECR). The process was continuously monitored by a mass spectrometer and the correspondent results show the formation of methanol. The ECR operated at 10 -6 torr assisted with a microwave source of 250 Watts of power; the magnetic field was developed with 300 Amp on Helmholtz coils. The mode of operation of plasma was in cusp, and the electron temperature was 6-eV reported by a single Langmuir probe. The mass spectrometry reported the presence of methanol. The catalysts characterization is reported in form of Scanning Electron Microscopy image, a Raman spectroscopy analysis, and the Electron Dispersive Spectroscopy (EDS).